Evaluating the effects of hospital wastewater treatment on bacterial composition and antimicrobial resistome - Meng, Yan; Xu, Yi; Hu, Dongping; Pan, Qiuxiang; Weng, Liangliang; Huang, Weiyi; Zhao, Jin; Lan, Wei; Shi, Qiucheng; Yu, Yunsong; Jiang, Yan (Frontiers in Microbiology, 2025)
Hospital wastewater treatment systems (HWTS) are crucial in reducing the spread of antimicrobial resistance genes (ARGs) and antibiotic-resistant bacterial pathogens in hospital wastewater. This study aims to evaluate the impact of HWTS on the changes of bacterial composition and the relative abundance of ARGs. We collected wastewater samples from influent and effluent in a university hospital, and performed metagenomic sequencing. The results showed that HWTS altered the bacterial composition, with a decrease in the proportion of Gammaproteobacteria. However, phylogenetic analysis of metagenome-assembled genomes showed that Mycobacterium and Zoogloea from influent and effluent had a close relationship. A total of 140 non-redundant ARGs were identified based on open reading fragments analysis, with beta-lactam and aminoglycoside resistance genes being the most prevalent. The relative abundance of ARGs generally decreased after wastewater treatment (p < 0.0001), with 70.0% of genes that conferring resistance to “last-resort” antibiotics being undetectable in the effluent. However, the relative abundance of quaternary ammonium compounds resistance genes increased in the effluent. We identified that 66.4% of ARGs were located on plasmids, and 17.9% of ARGs were adjacent to mobile gene elements (MGEs), suggesting their potential for mobility. Subsequent analysis showed that ARGs originating from plasmids and adjacent to MGEs were negatively associated with their relative abundance reduction. In conclusion, this study provides a comprehensive evaluation of the impact of HWTS on composition of bacteria and the relative abundance of ARGs, highlighting the importance of effective wastewater treatment in combating the spread of antimicrobial resistance.